Gerakan Sosial Keagamaan Pada Masyarakat Kota Dan Desa Di Era Digital Abad 21 - Muhammad Mahbub Al Basyari (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article examines socio-religious movements in urban and rural communities in the digital era of the 21st century. This study uses literature research methods through document analysis in the form of literature studies. Data collection techniques in this study used library research techniques, which were then analyzed using descriptive methods to examine the contents of a relevant document, book, article, or research result. The purpose of writing this article is to examine the religious social movements of urban and rural communities in the digital era of the 21st century. The conclusion is that currently the world's citizens are living in the 21st century which is full of social dynamics due to the development and digitization of information and communication technology. Everyone, like it or not, must have digital literacy skills in order to survive and not be left behind, including in carrying out the socio-religious movement. In modern society, it is often distinguished between rural communities (rural communities) and urban communities (urban communities). This difference actually has nothing to do with the notion of simple society, because in modern society, no matter how small a village, there must be influences from the city. In contrast, in affluent societies, the influence of the city is relatively non-existent. The distinction between rural communities and urban communities is essentially gradual. Religious social movements are collectively organized efforts of religious adherents to respond to socio-religious realities in order to change or maintain existing values ​​or beliefs. This process is a manifestation of the religiosity of a group of people. One example of a religious social movement that can be carried out by urban and rural communities is the religious social movement at the Majlis taklim institution.